Research of the interrelations between actors and strategic goals in decision making - Somogyi, Sándor; Novković, Nebojša; Zoran, Čulibrk (Acta Agraria Debreceniensis, 2009)
management, although there are many chiseled methodologies plenty of professional literature. The problem is more complex in strategic planning of regional communities – societies – of different range. These societies are very diverse, and accordingly the strategic goal setting can, and has to be very different than the strategic goal setting of enterprises.The group of methods for morphologic and structural analysis and the computer based MACTOR program could be used.The output data are presented in a large number of matrixes, vectors, graphs and histogram’s, which describe very fair the possible scenarios for preparation and decision making aboutstrategic plans.